FIGO 2018 stage IB endocervical adenocarcinomas: an international study of outcomes informed by prognostic biomarkers. Issue 2 (February 2021) - Stolnicu, Simona; Boros, Monica; Hoang, Lien; Almadani, Noorah; de Brot, Louise; Baiocchi, Glauco; Bonvolim, Graziele; Parra‐Herran, Carlos; Lerias, Sofia; Felix, Ana; Roma, Andres; Pesci, Anna; et al.
ABSTRACT : Objective : Prognostic factors for endocervical adernocarcinomas are well known, but little is known about prognostic biomarkers influencing outcome for the newly defined International Federation of Gynecology and Obstetrics (FIGO) 2018 IB sub‐stages. The aim of this study was to identify prognostic biomarkers influencing recurrence‐free and overall survival for FIGO 2018 stage IB cervical adenocarcinoma sub‐types. We sought to identify these factors using a large international multi‐institutional series of cases. Methods : Stage IB endocervical adenocarcinomas were retrospectively collected from nine international institutions; full slide sets (n=464) were used to assign prognostic biomarkers. Inclusion criteria were the following: FIGO stage IB endocervical adenocarcinomas with follow‐up in which all paraffin blocks/glass slides were available for review and/or additional studies and the patient was surgically treated from 1985 to 2019. The types of specimens included in the study were conizations, trachelectomies, and simple/radical hysterectomies with or without lymph node samples. We excluded in situ carcinomas, squamous cell carcinomas, adenosquamous carcinomas, tumors with a neuroendocrine component, carcinosarcomas, and any tumor showing clinical, macroscopic, or microscopic features suggesting a lower uterine segment, uterine corpus, or an adnexal primary origin. Tumors treated with neoadjuvant chemotherapy and/or radiation therapy were also excluded, as well as biopsies and loop electrosurgical excision procedures. Results : Of 464 cases, 225 (48%) were stage IB1, 177 (38%) were stage IB2, and 62 (13%) were stage IB3. Five‐year and 10‐year recurrence‐free survivals were statistically different among stage IB sub‐types (p=0.005). Silva pattern of invasion was significant for recurrence‐free survival at 5 and 10 years (p=0.04); overall survival and recurrence‐free survival were higher in human papillomavirus (HPV)‐associated cases (p=0.007 and p=0.001, respectively) and in cases without lymphovascular invasion (p=0.004 and p=0.00001, respectively). Factors that significantly influenced recurrence‐free survival were HPV‐independent status (p=0.05; HR 2.31; 95% CI 1.02 to 5.46), presence of lymphovascular invasion (p=0.011; HR 3.50; 95% CI 1.33 to 9.19), and presence of lymph node metastasis (p=0.016; HR 2.66; 95% CI 1.20 to 5.90). Conclusion : HPV status and the presence of lymphovascular invasion are prognosticators in stage IB endocervical adenocarcinoma sub‐types. These parameters should be included in future sub‐staging modifications of FIGO stage IB endocervical adenocarcinomas and in treatment strategies.